[Stefan J. Schierholz/Pál Uzonyi (Hgg.): Formenlehre. Berlin/Boston: De Gruyter 2022 (= Wörterbücher zur Sprach- und Kommunikationswissenschaft. Bd. 1.1), 851 Seiten (ISBN: 978-3-11-018472-3, geb., 199,95 Euro)] - Kalaš, Filip, 1993-
Recenzia jazykovedného a komunikačného slovníka.